Kajian Hukum Atas Gugatan Penetapan Pasangan Calon Oleh Komisi Pemilihan Umum Dalam Proses Pemilihan Kepala Daerah Langsung (Studi Kasus Putusan Mahkamah Agung Nomor 244 K/TUN/PILKADA/2018) - Ja’far Ja’far (Jurnal Hukum dan Kemasyarakatan Al-Hikmah, 2020)
Abstract Election of Regional Head is an embodiment of Article 1 Paragraph (2) of the Constitution. Through the elections, the people can determine who will determine their position as regional head. Therefore, in the implementation of the elections, it must be carried out directly, publicly, freely, confidentially, honestly and fairly in order to guarantee the purity of people's sovereignty. As for the problems in this paper are regional head elections in the Indonesian constitutional system, the mechanism for resolving regional head election disputes in the legislation, as well as judges' considerations in regional head election disputes in the Supreme Court ruling No. 244 K / TUN / PILKADA / 2018?This research is descriptive with a normative juridical approach. "The normative juridical approach is to emphasize the science of law with a focus on secondary data, in the form of primary, secondary and tertiary legal materials", and to complete the data carried out by gathering relevant materials and conducting library studies where data will then be analyzed juridical. the Election of regional heads in the Indonesian constitutional system, it was understood that the Regional Head Election in addition to being the best form of democracy in the implementation of democratization, the Regional Head Election was also a demand that was born as a follow-up to the political reform of the state administration. The mechanism for resolving disputes over regional head elections in connection with the authority granted to the Constitutional Court to examine and adjudicate cases in disputes over the determination of the results of votes in the regional head elections granted by the Law. Judge's consideration in the dispute over regional head election in Supreme Court decision No. 244 K / TUN / PILKADA / 2018, that the Evidence of Sumedang Regency KPU Decree No. 18 / PP.02.3-Kpt / 3211 / KPUKab / II / 2018 concerning Determination of Regent and Deputy Candidates The 2018 Regent of Sumedang, connected with the Dispute Resolution Decree No. 001 / PWSL / 13.25 / II / 2018, proved that the Plaintiff was not a Candidate Pair of Regent and Deputy Regent who met the 2018 requirements, based on the legal facts the Plaintiff filed a lawsuit in Jakarta PTTUN. Keywords          :    Legal Review, Lawsuit, Determination.          Abstrak Pemilihan Kepala Daerah merupakan perwujudan dari Pasal 1 Ayat (2) undang-Undang Dasar. Melalui pilkada, rakyat suatu daerah dapat menentukan siapa yang akan menduduki jabatan sebagai kepala daerah. Oleh karena itu, dalam pelaksanaan pilkada, harus dilaksanakan langsung, umum, bebas, rahasia, jujur, dan adil demi menjaga kemurnian kedaulatan rakyat.Adapun yang menjadi permasalahan dalam penulisan ini adaah Bagaimana pemilihan kepala daerah dalam sistem ketatanegaraan Indonesia?, Bagaimana mekanisme penyelesaian sengketa pemilihan kepala daerah dalam peraturan perundang-undangan?, serta Bagaimana pertimbangan hakim dalam sengketa pemilihan kepala daerah dalam putusan Mahkamah Agung Nomor 244 K/TUN/PILKADA/2018?Penelitian ini bersifat deskriptif dengan pendekatan yuridis normatif. “Pendekatan yuridis normatif yaitu menekankan pada ilmu hukum dengan menitik beratkan pada data sekunder, yang berupa bahan hukum primer, sekunder, dan tertier”, dan untuk melengkapi data dilakukan dengan mengumpulkan bahan-bahan yang relevan dan melakukan studi pustaka yang selanjutnya data akan dianalisis secara yuridis.Pemilihan kepala daerah dalam sistem ketatanegaraan Indonesia, dipahami bahwa Pemilukada di samping sebagai wujud demokrasi yang masih terbaik dalam penyelenggaraan demokratisasi, Pemilukada juga merupakan tuntutan yang lahir sebagai tindak lanjut reformasi politik ketatanegaraan. Mekanisme penyelesaian sengketa pemilihan kepala daerah sehubungan dengan kewenangan yang diberikan kepada Mahkamah Konstitusi untuk memeriksa dan mengadili perkara perselisihan penetapan hasil perolehan suara dalam pemilihan kepala daerah yang diberikan Undang-Undang. Pertimbangan hakim dalam sengketa pemilihan kepala daerah dalam putusan Mahkamah Agung No 244 K/TUN/PILKADA/2018, bahwa Bukti Surat Keputusan KPU Kabupaten Sumedang No 18/PP.02.3-Kpt/3211/KPUKab/II/2018 tentang Penetapan Calon Bupati dan Wakil Bupati Sumedang 2018, dihubungkan dengan Putusan Penyelesaian Sengketa No 001/PWSL/13.25/II/2018, terbukti Penggugat bukanlah Pasangan Calon Bupati dan Wakil Bupati yang memenuhi syarat Tahun 2018, berdasarkan fakta hukum Penggugat mengajukan gugatan di PTTUN Jakarta.Kata Kunci        :    Tinjauan Hukum, Gugatan, Penetapan.